Clinical Significance of Enterococcus Presence in Vaginal Discharge - Guevara Duncan, José (2000)
OBJECTIVES: To determine if presence of Enterococcus is related to pathological vaginal discharge (VD), as well its frecuency in VD, and its antimicrobial-resistance levels. MATERIALS AND METHODS: In a 4-month period were selected 98 women who attend to gynecological outpatient service due to VD; in samples of these VD leukocytes search, and isolation and culture procedures for Enterococcus and other female-genital-tract-associated microorganisms were performed. RESULTS: Enterococcus species, mainly E. faecalis were isolated from 39% of patients. Gardnerella vaginalis was identified in 44% of patients. Presence of enterococcus was associated with neither pathogeny nor anal intercourse. There was no penicillin-resistant Enterococcus strain. CONCLUSIONS: In the studied VD patients Enterococcus would not exert pathogenic activity, and was ranked 2th in frecuency after G. vaginalis. There was no in vitro penicillin-resistance among the 38 strains studied.